Pengaruh Kemampuan, Usaha dan Dukungan Organisasi terhadap Kinerja pegawai - Tri - Bodroastuti; Freddy Aldo Setiawan; Tjandra . Tirtono (Universitas Darussalam Gontor, 2020)
The purpose of this study was to analyze the effect of ability, effort and organizational support, on employee performance. The population in this study were all employees assigned to the Central Java Province BPPD office, amounting to 324 employees. The number of samples was calculated using the Slovin formula, and 80 respondents were obtained. The sampling technique used conveinence sampling. The analysis technique used is multiple liniear regression. Based on hypothesis testing both partially and simultaneously, ability, effort, and Organizational Support have a positive effect on the performance of employees.